2016
DOI: 10.2147/dddt.s117166
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin enhances the propagation of cortical spreading depression: comparative studies with sumatriptan and novel kynurenic acid analogues

Abstract: BackgroundThe complex pathophysiology of migraine is not yet clearly understood; therefore, experimental models are essential for the investigation of the processes related to migraine headache, which include cortical spreading depression (CSD) and NO donor-induced neurovascular changes. Data on the assessment of drug efficacy in these models are often limited, which prompted us to investigate a novel combined migraine model in which an effective pharmacon could be more easily identified.Materials and methodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Previous studies demonstrate that NTG administration causes a delayed migraine-like pain in migraineurs and an immediate headache in both migraine sufferers and healthy subjects (Ashina et al, 2013; Olesen, 2008; Thomsen et al, 1994). Because NTG-produced nitric oxide can modulate cortical spreading depression in humans and rodents (Petzold et al, 2008) and NTG can also enhance the propagation of cortical spreading depression (Knapp et al, 2017), the NTG-induced migraine model might display the cortical spreading depression-mediated aura. The administration of NTG not only triggers migraine in humans, but also produces cutaneous hyperalgesia in rodents (Ramachandran et al, 2012; Tassorelli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that NTG administration causes a delayed migraine-like pain in migraineurs and an immediate headache in both migraine sufferers and healthy subjects (Ashina et al, 2013; Olesen, 2008; Thomsen et al, 1994). Because NTG-produced nitric oxide can modulate cortical spreading depression in humans and rodents (Petzold et al, 2008) and NTG can also enhance the propagation of cortical spreading depression (Knapp et al, 2017), the NTG-induced migraine model might display the cortical spreading depression-mediated aura. The administration of NTG not only triggers migraine in humans, but also produces cutaneous hyperalgesia in rodents (Ramachandran et al, 2012; Tassorelli et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine, a proven blocker of SD, has been shown to stop the neurological aura symptoms in some patients but had no effect on the headache. 120 Many migraine drugs from different pharmacological classes have been tested against SD so far, 50,97,102,110,179,185,[192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207] and topiramate and flunarizine were most effective since they exerted an inhibitory effect in all of the revised studies.…”
Section: Anti-migraine Drugsmentioning
confidence: 99%
“…A dose-dependent reduction of the numbers and amplitude and a deceleration of KCl-induced SDs in isolated chicken retinas at a dosage from 0.05 to 2.00 mM 205,228 was observed in the late 1990s, while more recently published studies support these observations. 110,204 However, the scientific status of this agent is ambivalent, and some studies observed no reductive effect on SD. 194,203,229 Additional anti-migraine drugs that were effective against SDs are lamotrigine, 185 riboflavin, 185 methylsergide, 50,205 amitryptoline, 50 and propranolol, 50,205,206 but only a few experiments exist.…”
Section: Sumatriptanmentioning
confidence: 99%
“…Cortical spreading depression (CSD) is a self propagating wave in the cortical areas of the brain and it has a relevant role in the pathomechanism of migraine [ 52 ], as it is well accepted that CSD is the basis of the aura phenomena [ 53 ]. In the model of CSD, two new KYNA analogs inhibited the propagation of CSD waves [ 54 ], likely by the inhibition of glutamate receptors. Since glutamate receptors have a crucial role in the propagation and generation of CSD [ 55 ], they possibly represent a link between migraine and CSD.…”
Section: Kynurenine Pathway (Kp) and Migrainementioning
confidence: 99%